DIGITALIZATION WITH CITIZEN VERIFICATION AND CONTROL SYSTEM - Yuwadee Wongweeraprasert (PEOPLE: International Journal of Social Sciences, 2025)
Poverty remains an undeniable social issue that is deeply rooted in the social fabric. The state welfare card policy under the leadership of General Prayut Chan-o-cha was created as guidelines for improving life quality and ending poverty by helping with living expenses, finding opportunities to access public services, and developing vocational training.The state relies on specific identity representations in the neoliberal world in the absence of authentic empirical evidence. Perceptive ambiguities lead to an attempt to create a field of meaning that is static and numerable until it becomes a characteristic that the state can control and predict. The more it is combined with the proof mechanism, the more it is conducive to the growth of capital groups and political networks aggravating international poverty despite repeated suppression. Those uncounted or overlooked by the system are challenged for survival and activities that they are allowed to do. Results are that the state welfare card represents a set of governmental ideas with clear control and determination goals. Poverty and politics remain intertwined, as the card helps societal denizens learn to prove their own poverty and be aware of new rules by which poverty is reduced according to the state perception framework. As a result, the state welfare card is a basis for creating more poverty under the neoliberal drive.